Study the effect of hyperbaric oxygen therapy in Egyptian autistic children: A clinical trial - Farida El-baz; Reham M. Elhossiny; Yasser Abdel Azeem; Marianne Girgis (Egyptian Journal of Medical Human Genetics, 2014)
Background: Numerous studies of autistic individuals have revealed evidence of cerebral hypoperfusion, neuroinflammation, gastrointestinal inflammation, immune dysregulation, oxidative stress, relative mitochondrial dysfunction, and neurotransmitter abnormalities. Many of these findings have been correlated with core autistic symptoms. For example, cerebral hypoperfusion in autistic children has been correlated with repetitive, self-stimulatory and stereotypical behaviors, and impairments in communication. Specifically, hyperbaric oxygen therapy (HBOT) has been used and can compensate for decreased blood flow by increasing the oxygen content of plasma and body tissues. The aim of this work was to study the effect of hyperbaric oxygen therapy in autistic Egyptian children. Patients and methods: This prospective clinical trial study was conducted on 20 children diagnosed as autism based on DSM-IV-TR criteria (diagnostic and statistical manual of mental disorders, 4th edition criteria, text revised). All patients received at least 20 sessions of hyperbaric oxygen therapy. Sessions were done at pressure 1.5 ATA (atmosphere absolute) with 100% oxygen concentration each lasting for 1–1.5 h either in multiplace chamber or monoplace chamber. MRI Perfusion of the brain was done before and after at least 20 HBOT sessions only for 6 cases. Results: There was a statistically significant increase in the ratio of regional cerebral blood flow (RCBF) to white matter after HBOT in different brain regions when compared to their levels before HBOT. Conclusion: HBOT is a treatment that has recently become quite popular in the autism spectrum disorder (ASD) community. Its benefits cross a wide range of autistic traits as: improved language, increased awareness, behavior and socialization by affecting the pathophysiological findings in autism.